KONSENTRASI PACLOBUTRAZOL DAN PEMISKINAN MEDIA PADA PELESTARIAN IN VITRO TANAMAN KRISAN (Chrysanthemum morifolium Ramat) - Demmassabu, Sofia; Kojoh, Diane A.; Arsyad, Yulie P. (EUGENIA, 2011)
ABSTRACT   Research was conducted  at biotechnology laboratory of Agriculture Faculty, Samratulangi University Manado since July 2009 until October 2009. The objective was to assess the effect of Paclobutrazol usage and MS media reducing in chrysan perpetuation through in vitro. The research was  designed in randomized complete designed  using factorial. First factor was basic media concentration of Murashige and Skoog with 2 concentration : M1 = 100% MS,  M2 = 10% MS and second factor was paclobutrazol with 4 concentration s which were  P0 = 0 ppm paclobutrazol (control), P1 = 1.0 ppm, P2 = 1.5 ppm, P3= 2.0 ppm,  and P4 = 2.5 ppm paclobutrazol.  The treatments were repeated ten times.  Observed variables were crysan tall, the amount of root and buds that was measured at the end of research. The result showed that 100 % MS media, addition of paclobutrazol obviously produced shorter chrysan, and less amount of roots and buds compare to media without paclobutrazol. Media with 10 % MS combine with   paclobutrazol 2.0 ppm produced shorter chrysan than media without paclobutrazol. The amount of roots and buds in media with paclobutrazol were not different with media  without paclobutrazol. Key words : Paclobutrazol, crysan